EP-642 Case Report: Using the Novel Flamingo Device for Endoscopic Treatment of Buried Bumper Syndrome in high risk patients. (9th August 2022) - Asnani, Kusum; Fernandes, Roland
Abstract: Aim: Buried Bumper Syndrome is a rare, major late complication of percutaneous endoscopic gastrostomy (PEG) occurring in 1% of cases. It occurs when the internal bumper of the PEG tube erodes into the gastric wall. This lead to a loss of patency, leakage and inability to change the tube endoscopically. Until recently, the treatment was surgical removal under general anaesthesia. However, patients with BBS are likely to have significant co-morbidities thus deeming the procedure high risk. Method: We present a case report demonstrating successful treatment of BBS completed endoscopically using the Flamingo device with a good patient outcome. The Flamingo device is a new endoscopic tool that acts like a sphincterotome. Appropriate consent was taken from the patient. This was performed on a 56 year old patient suffering from multiple sclerosis causing dysphagia for which a PEG tube was inserted in 2018 for nutrition. Over time, his care home noticed significant leakage from the site. At gastroscopy, he was diagnosed with BBS. Due to his risk for surgical intervention, the Flamingo device was trialled to remove the buried bumper and allow insertion of a new PEG. Results: As demonstrated in the photos, the mucosa was successfully cut allowing the buried bumper PEG to be retrieved. A new PEG was inserted without complication. The patient was discharged the following day and no complications have arisen 3 months later. Conclusion: The Flamingo device has proven to be a safe and minimally-invasive method to treat BBS endoscopically in this patient.